Antibacterial Activities and Mechanism of Action of Acetone Extracts from Rabdosia rubescens - Li Ping Cheng; Qing Ping Hu (Aceh International Journal of Science and Technology, 2015)
The antibacterial activities and mechanism of action of acetone extracts from R. rubescens were reported in this paper. The results showed that 80% acetone extracts had both the highest contents of total phenolics and flavonoids. Acetone extracts showed better antibacterial activities against Gram-positive bacterial strains and there were no inhibitory effects found on tested Gram-negative bacteria. In addition, 80% acetone extracts from R. rubescens had relatively higher antibacterial activities with the lowest values of MIC and MBC at 2.5 mg/mL and 5 mg/mL against B. subtilis. The antibacterial mechanism of 80% acetone extracts against Bacillus subtilis might be described as disrupting cell wall, increasing cell membrane permeability, and finally leading to the leakage of cell constituents